Improving cervical cancer screening in Mexico: results from the Morelos HPV Study - Flores Yvonne; Bishai David; Lazcano Eduardo; Shah Keerti; Lörincz Attila; Hernández Mauricio; Salmerón Jorge; Ferris Daron; Hernández Pilar; Sherman Mark E; Ronnett Brigitte M; Carmona Enrique; et al. (Salud Pública de México, 2003)
OBJECTIVE: The purpose of this paper is to describe some of the results of the Morelos HPV Study. The main objective of the Morelos HPV Study is to evaluate the use of human papillomavirus (HPV) DNA testing, as compared to the Papanicolaou (Pap) test, for cervical cancer (CC) screening. MATERIAL AND METHODS: The Morelos HPV Study is currently being conducted in Mexico, to examine the possibility of using HPV testing for CC screening. The HPV testing of self-collected vaginal and clinician-collected cervical specimens was evaluated as part of this study. The acceptability of the HPV testing of self-collected specimens was compared to that of the Pap test. A cost-effectiveness analysis (CEA) and cost-benefit analysis (CBA) was also performed. RESULTS: The Morelos HPV Study results indicate that HPV testing has a greater sensitivity to detect cervical intraepithelial neoplasia (CIN) 2/3 and CC than the Pap test. Our results also indicate an over-all lower acceptability of the Pap test as compared to the self-collected procedure. The results of the CEA and CBA indicate that screening women between the ages of 20-80 for CC using some type of HPV testing is always more cost-effective than screening for CC using the Pap test. CONCLUSIONS: Our results suggest that self- and clinician-collected HPV testing could be used in CC prevention programs, as an effective complement or substitute for the Pap test.